Integrasi Nilai-Nilai Karakter Dalam Pembelajaran Pendidikan Jasmani, Olahraga, Dan Kesehatan (PJOK) Di Jenjang Sekolah Dasar - Anindya Syifa Nuraini; Haifa Annisa; Ismi Rahmayanti; Lailatul Qurrota Ayuni; Naila Zahra Nur Makiyyah; Siti Nur Aprilianti; Agus Mulyana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Character education is a fundamental element in the educational process, especially at the elementary school level where students are at the critical stage of forming values ​​and principles. At this age, students are experiencing rapid physical, mental, emotional and social development. Therefore, character education is very important to help students build strong moral and social foundations. In the context of Physical Education, Sports and Health (PJOK) subjects, the integration of character values ​​not only enriches the curriculum but also strengthens students' moral and social foundations. PJOK's diverse and dynamic activities, such as games, sports and other physical activities, provide an ideal platform for instilling important values ​​such as honesty, discipline, cooperation, responsibility and sportsmanship. Through a systematic and reflective approach, this research identifies effective methods for integrating these values ​​into daily PJOK activities. This includes developing a curriculum designed to promote positive social interactions, increased self-awareness, and appreciation for diversity and inclusion. For example, in team games, students can learn about cooperation, communication, and mutual respect. In individual activities, students can develop self-discipline, responsibility, and sportsmanship. Additionally, teachers can facilitate reflective discussions after activities to help students understand and internalize the values ​​they have put into practice. By systematically integrating character education in PJOK subjects, this research aims to help students not only develop physical abilities, but also build strong character, which will be the foundation for their future development. And thus, PJOK learning does not only focus on physical development but also on strengthening character, which ultimately forms students who are holistically healthy - both physically and socially-emotionally. This research provides new insights into the potential of PJOK learning as a tool for character education, offers concrete strategies for educators to implement these values ​​effectively, and highlights the importance of integrated character education in the elementary school curriculum.